2020
DOI: 10.3390/mti4040088
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Production in Elicitation Studies and the Legacy Bias-Consensus Trade off

Abstract: Gesture elicitation studies are a popular means of gaining valuable insights into how users interact with novel input devices. One of the problems elicitation faces is that of legacy bias, when elicited interactions are biased by prior technologies use. In response, methodologies have been introduced to reduce legacy bias. This is the first study that formally examines the production method of reducing legacy bias (i.e., repeated proposals for a single referent). This is done through a between-subject study th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…However, they categorized gestures as being infuenced by legacy bias only if participants verbally mentioned they were infuenced by prior technology during the study. In comparison, Williams et al [55] categorized a proposed gesture as a legacy or non-legacy gesture through a consensus of independent votes of three expert raters if the gesture class could be identifed as being used with a known device in common usage. In their study, they found that increased production reduced consensus on proposals and was effective in reducing legacy bias by about 12% for those referents that were most likely to be infuenced by bias in the frst place.…”
Section: Discussion 61 the Impact Of Unlimited Production On Elicitationmentioning
confidence: 99%
See 3 more Smart Citations
“…However, they categorized gestures as being infuenced by legacy bias only if participants verbally mentioned they were infuenced by prior technology during the study. In comparison, Williams et al [55] categorized a proposed gesture as a legacy or non-legacy gesture through a consensus of independent votes of three expert raters if the gesture class could be identifed as being used with a known device in common usage. In their study, they found that increased production reduced consensus on proposals and was effective in reducing legacy bias by about 12% for those referents that were most likely to be infuenced by bias in the frst place.…”
Section: Discussion 61 the Impact Of Unlimited Production On Elicitationmentioning
confidence: 99%
“…[33]. Existing research has produced contradictory outcomes on the efect of increased production on legacy gestures [20,33,55]. We ofer a slightly diferent interpretation: that those minor variations are not irrelevant, and that these latter proposals are refnements of prior gestures which preserve the gestural features that matter most to users.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Many of the atomic gestures, such as the dragging and splay gesture for T-19 and T-1, are taken from the screen-based interactions. As demonstrated by a fair number of existing studies, legacy bias is a contributing factor that users generate personally satisfying designs [58], [59], [60]. Due to the conscious use of previous knowledge [61], the designs that successfully leverage legacy bias can have a positive impact on their performance.…”
Section: B Design Suggestionsmentioning
confidence: 99%